Optimisation des efforts serre-flan pour l’emboutissage d’une boîte carrée: Contrôle de la striction et du plissement sous serre-flan - Ben Ayed, Lanouar; Delamézière, Arnaud; Batoz, Jean-Louis; Knopf-Lenoir, Catherine (European Journal of Computational Mechanics, 2006)
The goal of numerical simulation in sheet metal stamping is mainly the improvement of the quality of the final part achievable by the control and the optimization of process parameters. To avoid the failure, a localised necking criterion is formulated and validated on a cylindrical cup and a Nakazima test, on which failures were observed experimentally. The second part of the paper is devoted to the optimization of the blankholder forces in the case of square-cup deep drawing in order to improve its formability.